Sulfated Ligands for the Copper(I)-catalyzed Azide-Alkyne Cycloaddition - Wang, Wei (2011)
The copper(I)-catalyzed azide-alkyne cycloaddition, the most widely recognized reaction of click chemistry, is accelerated by tris(triazolylmethyl)amine-based ligands. Here, we compared two new ligands in this family, BTTP and the corresponding sulfated ligand BTTPS, for three bioconjugation applications: (1) labeling of alkyne-tagged glycoproteins in crude cell lysates, (2) labeling of alkyne/azide-tagged glycoproteins on the surface of live mammalian cells, and (3) labeling of azides in surface proteins of live Escherichia coli. Though BTTPS exhibits faster kinetics than BTTP in accelerating the CuAAC in in vitro kinetic measurements, its labeling efficiency is slightly lower than BTTP in conjugating biomolecules bearing a significant amount of negative charges due to electrostatic repulsion. Nevertheless, the negative charge conferred by the sulfate at physiological conditions significantly reduced the cellular internalization of the coordinated Cu(I), thus making BTTPS-Cu(I) a better choice for live cell labeling.